PENATALAKSANAAN FISIOTERAPI PADA KASUS DOWN SYNDROME - Oktarina, Mona; Mailani, Rena; Adzkya, Nandysa (Indonesian Journal of Physiotherapy, 2024)
Down Syndrome is a genetic disorder that occurs due to an extra chromosome 21. This condition causes various developmental problems, such as motor delays, muscle hypotonia, and cognitive and social limitations. Based on data from the World Health Organization (WHO), the prevalence of Down Syndrome in the world reaches around 1 case per 1,100 births. Physiotherapy management is an important part of helping children with Down Syndrome to develop motor skills, improve postural function, and improve quality of life. The patient aged 3 years and 5 months with Down Syndrome had delayed motor development, including not being able to walk independently, although he could sit stably and roll over. Clinical examination revealed muscle hypotonia, unstable posture, and limited joint range of motion. The patient had joint hypermobility characterized by asymmetrical posture and postural muscle weakness. The patient's diagnosis is Down Syndrome (Trisomy 21). Physiotherapy interventions provided include Neurodevelopment Treatment (NDT) to improve postural control and body stability, play therapy for fine and gross motor stimulation, sensory treatment to stimulate the sensory motor system, and positioning exercises to improve posture and joint stability. After three therapy sessions, there were significant improvements in the patient's ability to stand more stably, reduction of muscle hypotonia, and improved gross motor control. The success of physiotherapy intervention in patients with Down Syndrome depends on the consistency of ongoing therapy and the active role of parents in performing exercises at home. This shows the importance of collaboration between the physiotherapist and the patient's family to support the child's optimal development. Keywords: Physiotherapy, Down Syndrome, Neurodevelopment Treatment, play therapy, sensory.